Species distributions models: A synthetic revision - Mateo, Rubén (2011)
In the last years a new tool has become widely used in ecological studies: species distribution models. These models analyze the spatial patterns of presence of organisms objectively, by means of statistical and cartographic procedures based on real data. They infer the presence of potentially suitable areas according to their environmental characteristics. Data stored in natural history collections can be used for this purpose, which gives new opportunities to use to these types of data. The models have evolved from the analysis of single species to the study of hundreds or thousands of taxa which are combined for the assessment of biodiversity and species richness. In this paper we review the variety of methods used, their potential and weaknesses, and the limiting factors that influence the interpretation of species distribution models.